Inhibition activity of Saccharomyces boulardii and Lactobacillus acidophilus against pathogenic E.coli isolates from Recurrent Urinary Tract Infection in women In Vitro (Baghdad Science Journal, 2014)
The aims of study is to detect the inhibitory effect of Saccharomyces boulardii and Lactobacillus acidophilus on Escherichia coli that has been isolated from recurrent urinary tract infection in women. The sensitivity of E.coli isolates to antibiotics had been studied and the most resistant E.coli isolate to antibiotics had been studied .The cup assay was used on nutrient agar and Muller-Hinton agar to detect the inhibitory activity for each S.boulardii yeast grown on YEGP media and L.acidophilus grown on MRS media in which the result showed a high inhibition activity for each of them .Also in this study the adhesion property of E.coli had been evaluated in the presence of S.boulardii at concentration of 1×109 and L.acidophilus at concentration of 1×106. Result revelead that both of them inhibit the adhesion of E.coli at 72.73% and 64.91% , respecherely these concentrations was used to measure the bacteriocin activity produced by L.acidophilus and inhibitory compounds produced by S.boulardii.The result showed there were no growth for E.coli colonies after 48 hrs of incubation.